(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe study was conducted in Baghdad and aimed to:The impact of moving the educational activities in the conservation of literarytexts and the development of literary taste in the fifth grade students moral "byverifying the validity of hypotheses Elsafreeten following forms:The first hypothesis:- There are no differences in women with statistical significance between meansof scores of students three experimental groups, the experimental group firstused upstream activities in the teaching material of literature and texts, thesecond experimental group used the activities of building in the teachingmaterial itself and the experimental group the third use activities concludingtaught the same course at Save literary texts.The second hypothesis:- There are no differences in women with statistical significance between meansof scores of students three experimental groups, the experimental group firstused upstream activities in the teaching material of literature and texts, thesecond experimental group used the activities of building in the teachingmaterial itself and the experimental group the third use activities concludingtaught the same course at test of literary taste.To achieve the goal of research and Frdite; the researcher experimental designwith three groups of animate post test only, then set the research community andappointed as consisting of the research community of students in fifth gradeliterature in middle school and high school day in the city of Baghdad, where thenumber of students (130) Student, and are randomly simple three were chosen asexperimental groups, were excluded (10) students statistically because of failurein the classroom the same three experimental groups, bringing the number ofstudents are (120) student, and then rewarded by the researcher between thethree experimental groups to find statistically significant in some of the variablesthat may affect the results of the experiment, it was rewarded by a researcher atthe chronological age of the students and academic achievement for the fatherand mother as well as the pretest of the skill of tasting moral, before applying the